Design and Implementation of an Educational Program in Advanced Airway Management for Anesthesiology Residents - Zana Borovcanin; Janine R. Shapiro (Anesthesiology Research and Practice)
Education and training in advanced airway management as part of an anesthesiology residency program is necessary to help residents attain the status of expert in difficult airway management. The Accreditation Council for Graduate Medical Education (ACGME) emphasizes that residents in anesthesiology must obtain significant experience with a broad spectrum of airway management techniques. However, there is no specific number required as a minimum clinical experience that should be obtained in order to ensure competency. We have developed a curriculum for a new Advanced Airway Techniques rotation. This rotation is supplemented with a hands-on Difficult Airway Workshop. We describe here this comprehensive advanced airway management educational program at our institution. Future studies will focus on determining if education in advanced airway management results in a decrease in airway related morbidity and mortality and overall better patients’ outcome during difficult airway management.